Peripheral vascular remodeling during ischemia - Lin, Shigang; Lin, Ruoran; Zhang, Hongkun; Xu, Qingbo; He, Yangyan (Frontiers in Pharmacology, 2022)
About 230 million people worldwide suffer from peripheral arterial disease (PAD), and the prevalence is increasing year by year. Multiple risk factors, including smoking, dyslipidemia, diabetes, and hypertension, can contribute to the development of PAD. PAD is typically characterized by intermittent claudication and resting pain, and there is a risk of severe limb ischemia, leading to major adverse limb events, such as amputation. Currently, a major progress in the research field of the pathogenesis of vascular remodeling, including atherosclerosis and neointima hyperplasia has been made. For example, the molecular mechanisms of endothelial dysfunction and smooth muscle phenotype switching have been described. Interestingly, a series of focused studies on fibroblasts of the vessel wall has demonstrated their impact on smooth muscle proliferation and even endothelial function via cell-cell communications. In this review, we aim to focus on the functional changes of peripheral arterial cells and the mechanisms of the pathogenesis of PAD. At the same time, we summarize the progress of the current clinical treatment and potential therapeutic methods for PAD and shine a light on future perspectives.